Germy science : the sick truth about getting sick (and staying healthy) - Kay, Edward (Kay, Edward. Gross science book., 2021)
"This hilarious, thoroughly researched book explains exactly how the microorganisms we know as germs are responsible for so much grossness. Kids will learn all about what germs (a general term for four specific microorganisms) actually are, how we get sick, how the human immune system works, and the best ways to stay healthy. Humans have gone from not knowing germs existed to using them to help lessen the effects of climate change. As readers delve into this history, they'll be fascinated by revolting stories (featuring corpse catapults, shaved chicken butts, and more) from the most influential plagues and pandemics in history. At a time when we've all had to become germ experts, this book is a perfect pick for budding young scientists."--